2020
DOI: 10.1155/2020/6678503
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Characteristics of Breast Cancer Patients Treated with Chemotherapy

Abstract: Introduction. Patients receiving chemotherapy for breast cancer may be at risk of developing cardiac dysfunction and electrophysiological abnormalities. The aim of this study is to evaluate alterations in electrocardiographic (ECG) parameters in breast cancer patients receiving chemotherapy. Materials and Methods. This was a prospective single-center cohort study conducted in the Fourth Hospital of Hebei Medical University, China. Participants with breast cancer referred for chemotherapy from May 1, 2019, to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…myocardial fibrosis, the proportion of fQRS was also increased significantly after chemotherapy in patients with DLBCL (15.8% to 28.9%, p = .041) and breast cancer (26.6% to 53.1%, p < .01; Chen et al, 2020;Das et al, 2008;Liang et al, 2020). However, the clinical significance of fQRS may vary depending on its different distribution in the coronary artery territory.…”
Section: Discussionmentioning
confidence: 96%
“…myocardial fibrosis, the proportion of fQRS was also increased significantly after chemotherapy in patients with DLBCL (15.8% to 28.9%, p = .041) and breast cancer (26.6% to 53.1%, p < .01; Chen et al, 2020;Das et al, 2008;Liang et al, 2020). However, the clinical significance of fQRS may vary depending on its different distribution in the coronary artery territory.…”
Section: Discussionmentioning
confidence: 96%
“…More importantly and based on a mechanistic point of view, identification of fQRS in breast cancer [ 10 , 11 ] and non-Hodgkin lymphoma patients treated with R-CHOP regimens [ 12 ] were the drivers that prompted our interest in conducting this pilot analysis among an unselected group of MM patients, at different stages of their treatment, particularly when the incidence of MM has continued to increase based on findings recently published from studies assessing the global burden of MM since 1990 [ 23 ]. Furthermore, the undeniable reality that MM is occurring in younger patients (median age at diagnosis 70 years old [ 14 , 23 , 24 ] is critically important as MM clinical outcomes, not only are these dependent on each individual patient's overall fitness and underlying health status but also, age with a recognized cut off < 65 years, is a good prognostic marker [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fQRS was later identified among 40.8% of non-Hodgkin lymphoma patients treated with R-CHOP regimens [ 12 ]. Based on these findings, the investigators conducting this study proposed that the development of the fQRS pattern in response to cancer therapy might be considered as a potential new tool for the noninvasive assessment of potentially related chemotherapy-induced cardiotoxicities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The prevalence of fQRS ranges from 1% to 30% in the general population, with a much higher prevalence in cancer patients after treatment with chemotherapy. 24 Given that myocardial fibrosis is an adverse effect of cancer therapy and chemotherapies can trigger apoptosis or necrotic myocyte death, studies have reported the importance of fQRS to recognise chemotherapy-related cardiotoxicities even preceding development of cardiac symptoms or echocardiographic abnormalities. 25,26…”
Section: Ventricular Conduction Abnormalities: Qrs Fragmentation and ...mentioning
confidence: 99%